Population and Economic Growth - Becker, Gary S; Glaeser, Edward L; Murphy, Kevin M (American Economic Review, 1999)
This paper examines the relationship between population and economic growth. It analyzes the implications of the effects of higher population density on per capita incomes and other variables in different countries and other geographic regions. Several statistical models that interpolate population to cities investment in human capital and economic growth were utilized to help analyze population growth. Generally economists along with others have believed that higher population lowers per capita incomes by diminishing returns. On the contrary there are few proofs demonstrating that higher population in more developed economies reduce per capita incomes. Population may reduce productivity secondary to traditional diminishing returns from more intensive use of land and other natural resources. However large populations encourage greater specialization and increased investments in knowledge. Therefore the net relation between greater population and per capita incomes relies on whether the inducements to human capital and expansion of knowledge are stronger than diminishing returns to natural resources.